Analysis of factors influencing demand for tourism in South Sulawesi - Husnul Khatimah; Anas Iswanto Anwar; Sri Undai Nurbayani (Institute of Computer Science (IOCS), 2023)
Tourism is an asset for a region or a country whose existence can create a people's economy and promote creative industries through tourist demand for tourism. However, the presence of the Covid-19 virus has paralyzed tourism activities due to lack of demand. This study aims to determine several conditions that can influence tourists to make tourism requests, including income, facilities, travel costs, leisure time and promotions. This research was conducted in South Sulawesi (Bira beach tourism object and Malino pine forest). The analytical method used is multiple linear regression using primary data obtained from distributing questionnaires. The data were processed using IBM statistics 23 software. The results showed that the variables of income, facilities, travel cost, leisure time and promotions in this study had a significant and positive effect. The economic value of the consumer surplus of bira beach tourists is IDR 854,179 per individual per visit and a total economic value of IDR 385,392,752,115/year is obtained and the consumer surplus of Malino pine forest tourists is IDR 616,364 per individual per visit and a total economic value of IDR 202,691 is obtained. 917,764/year.